2011
DOI: 10.1002/adem.201000312
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Nanograined Fe–C Alloys after Severe Plastic Deformation

Abstract: The microstructure and properties of several Fe–C alloys are studied in a) the as‐cast state, b) after a long annealing time at 725 °C, and, c) after high‐pressure torsion (HPT) The grain size after HPT is in the nanometer range. Only Fe3C (cementite) and α‐Fe remain in the alloys after HPT. Less stable Hägg carbide and retained austenite disappear after HPT, and phase composition closely approaches the equilibrium corresponding to the HPT temperature and pressure. This HPT behavior differs from that associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…It has been reported that XRD is not able to detect grain boundary segregations or complexions [51][52][53]. It has been shown that the phase boundaries are changed compared to the generally accepted phase diagrams for example in Cu-Bi [54,55], W-Ni [56] and Mo-Ni [56] by as much as 0.08 at.% Bi, 0.31 at.% Ni and 1.7 at.% Ni, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…It has been reported that XRD is not able to detect grain boundary segregations or complexions [51][52][53]. It has been shown that the phase boundaries are changed compared to the generally accepted phase diagrams for example in Cu-Bi [54,55], W-Ni [56] and Mo-Ni [56] by as much as 0.08 at.% Bi, 0.31 at.% Ni and 1.7 at.% Ni, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…It is noted that oxide phase was not detected by X-ray diffraction either in the initial powder or in the consolidated specimens which can be explained by its small fraction (0.2-1% as calculated from the particle size and the oxide layer thickness) and/or its amorphous state. Additionally, the observation of this oxide phase is more difficult if it does not form dispersoids during sintering but rather remains in the form of a thin grain boundary layer, similar to carbides in steel after HPT [36] or MnO in Mn-doped nanograined ZnO [37].…”
Section: Resultsmentioning
confidence: 98%
“…[19][20][21] This can be related to the fact that the maximum investigated strains were not large enough to induce a dissolution. The maximum nominal shear angle c investigated in this study was approximately~28 (e vM~1 6), whereas the largest nominal shear angle investigated in Reference 19 was approximately c~400.…”
Section: A Microstructure and Hardnessmentioning
confidence: 94%